Serum lipid profile in systemic lupus erythematosus - Xuan, Jingxiu; Deng, Chaoqiong; Lu, Huiqin; He, Yan; Zhang, Jimin; Zeng, Xiaoli; Sun, Yuechi; Chen, Shiju; Liu, Yuan (Frontiers in Immunology, 2025)
BackgroundDyslipidemia presents in various autoimmune diseases, and the serum lipid profile in systemic lupus erythematosus (SLE) has not yet been clearly defined. This study aims to evaluate the level of serum lipids in patients with SLE.MethodsA case–control study evaluated four conventional sera lipids—total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL)—in patients with SLE compared to healthy controls (HCs). Correlations between serum lipids and clinical characteristics were analyzed in patients with SLE. A systematic review and meta-analysis were conducted to assess the epidemiology of lipid profiles in patients with SLE, and a random-effects meta-analysis was performed for data synthesis.ResultsTC and TG were elevated significantly, and HDL decreased in patients with SLE compared to HCs. Elevated lipids were associated with progressive disease activity. TC, TG, and HDL were elevated in patients with SLE and were associated with decreased IgG, increased 24-h proteinuria, white blood cells (WBCs), and neutrophils. Decreased HDL and increased TG were associated with an increase in the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI). Patients with SLE who took glucocorticoids (GCs) may have experienced increases in TC and TG, while those who took hydroxychloroquine (HCQ) may have experienced increases in TC and HDL. Eleven eligible studies including the present study on associations between serum lipids and SLE were reviewed by the meta-analysis. The results demonstrated elevated TC (MD = 0.85, 95% CI 0.82 to 0.89, p < 0.00001) and TG (MD = 0.96, 95% CI 0.94 to 0.99, p < 0.00001) levels in SLE, while HDL decreased (MD = −0.19, 95% CI −0.20 to −0.17, p < 0.00001).ConclusionsDyslipidemia is present in SLE. There was a significant association between SLE disease activity and TC, TG, and HDL. The exact pathogenesis of metabolic disorders in SLE needs to be further addressed.